Functional disruption of cell wall invertase inhibitor by genome editing increases sugar content of tomato fruit without decrease fruit weight - Kohei Kawaguchi (Nature Portfolio, 2021)
Abstract Sugar content is one of the most important quality traits of tomato. Cell wall invertase promotes sucrose unloading in the fruit by maintaining a gradient of sucrose concentration between source leaves and fruits, while invertase inhibitor (INVINH) regulates this process. In this study, knock-out of cell wall INVINH in tomato (SlINVINH1) was performed by genome editing using, CRISPR/Cas9 and Target-AID technologies. Most of the genome-edited lines set higher soluble solid content (SSC) fruit than the original cultivar ‘Suzukoma’, while fruit weight was different among the genome-edited lines. From these genome-edited lines, three lines (193–3, 199–2, and 247–2), whose SSC was significantly higher than ‘Suzukoma’ and fruit weight were almost the same as the original cultivar, were selected. The fruit weight and overall plant growth of the two lines were comparable to those of the original cultivar. In contrast, the fructose and glucose contents in the mature fruits of the two lines were significantly higher than those of the original cultivar. The mature fruits of genome edited line 193–3 showed the highest sugar content, and the fructose and glucose contents were 29% and 36% higher than that of the original cultivar, respectively. Whole genome sequence data showed no off-target mutations in the genome-edited lines. Non-target metabolome analysis of mature fruits revealed that fructose was the highest loading factor in principal component analysis (PCA) between the genome-edited line and the original cultivar, and no unexpected metabolites appeared in the genome-edited line. In this study, we succeeded in producing tomato lines with high sugar content without a decrease in fruit weight and deterioration of plant growth by knock-out of SlINVINH1 using genome editing technology. This study showed that functional disruption of SlINVINH1 is an effective approach to produce tomato cultivars with high sugar content.